On-Call Duties: The Perceived Impact on Veterinarians' Job Satisfaction, Well-Being and Personal Relationships - Kogan, Lori; Schoenfeld-Tacher, Regina; Carney, Patrick; Hellyer, Peter; Rishniw, Mark (Frontiers in Veterinary Science, 2021)
Objective: To assess the impact of on-call duties on veterinarians' job satisfaction, well-being and personal relationships. Design: Cross-sectional survey. Sample: The sample was obtained from Veterinary Information Network (VIN) members in private practice within the United States. Procedures: A link to an anonymous online survey was distributed via an email invitation to all Veterinary Information Network (VIN) members with access from August 15, 2017 to October 21, 2017. Results: A total of 1,945 responses were recorded. The majority of those who reported having on-call duties were female associates. Composite scales were created to assess the impact of on-call shifts on job satisfaction and well-being. Multiple linear regression was conducted and found that gender (p = 0.0311), associate status (p < 0.0001), and age (p = 0.0293) were all significantly associated with on-call related job satisfaction. Additionally, multiple linear regression found that gender (p = 0.0039), associate status (p < 0.0057), and age (p < 0.0001) were all significantly associated with on-call related well-being. On-call shifts were reported by many to have a negative impact on job satisfaction and well-being; this was especially pronounced for female associates. Females had on-call related job satisfaction scores that were, on average, 1.27 points lower than that of males (lower scores equates to lower job satisfaction). Further, females' average on-call related well-being scores were 1.15 points higher than that of males (lower scores equates to higher well-being). Conclusions and Clinical Relevance: This study suggests that on-call shifts have a negative impact on veterinarian job satisfaction, well-being and personal relationships. The negative impact on job satisfaction and well-being is greatest for female associates. Veterinary medicine has been identified as a stressful occupation that can lead to psychological distress. It is therefore important to critically assess current practices that appear to increase stress and reduce emotional well-being. For this reason, it is suggested that veterinary hospitals explore alternative options to traditional on-call shifts.